Standar Desain Kamar Tidur Ramah Disabilitas - I Nyoman Andy Armawan; A. A. Ngurah Agung Reditya Ananta Surya; Gede Riki Prawira; Komang Deddy Endra Prasandya; I Wayan Runa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Persons with disabilities are those who have special treatment in carrying out daily activities, although nowadays various tools are available that can support their activities. However, this is not fully provided a bright light for persons with disabilities, they still need additional facilities, especially in the environment around them. The purpose of this research is to produce standard design for persons with disabilities, especially in the bedroom, the hope is this standard design can make it easier for them to move and reach certain points. The method used is to conduct a study of disability tools that are often used in the bedroom, this is to make it easier to determine the ideal size in the manufacture of furniture and other tools. The results of the study indicate that this design standard for persons with disabilities is proven to be able to facilitate their mobility when doing activities indoors.